DAMPAK VARIABEL MAKROEKONOMI DAN INDEKS SAHAM GLOBAL TERHADAP INDEKS HARGA LQ45 DI BURSA EFEK INDONESIA - MN, Nuryasman; Permatasari, Verencia (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2016)
The objective of this research was to examine the macroeconomics variable and global stock price index that influencing LQ45 stock price. There were three fundamental macroeconomics variables in this study such as Exchange rate of Rupiah, Interest Rate (SBI), and gold prices which used with global stock price index (Dow Jones Industrial Average) to examine their influence to LQ45 stock price.The sampling data used are 69 months from 2009 January until 2014 September. The selection ofthe sample usedisa non-probability sampling method, using purposive sampling technique. The method usedis multiple regression analysis and Error Correction Model (ECM)using softwareEviews6.0witha significance level of5%. The result of t-test show that gold prices have not influence LQ45 stock price. While the Exchange rate of Rupiah, Interest Rate (SBI), and Dow Jones Industrial Average have influence LQ45 stock price.The result of F- test (jointly test) showthat there are significantjointlybetween Exchange rate of Rupiah, Interest Rate (SBI), gold price, and Dow Jones Industrial Averageon LQ45 stock price.The result of ECM Models show that Â between Exchange rate of Rupiah, Interest Rate (SBI), gold price, and Dow Jones Industrial Averageon LQ45 stock price, there was notable toachieve abalance inthe long run.